1970
DOI: 10.4314/aja.v8i2.187578
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variations of the vertebral artery in a Zambian indigenous adult population undergoing computerised tomography angiography at the university teaching hospitals Lusaka, Zambia

Abstract: Vertebral artery is an important source of blood supply to the brain which arises from the subclavian arteries. Anatomical variations have been incidentally reported during autopsy and angiograms. These variations predispose to development of aneurysms, dissections and may lead to vertebrobasilar ischaemia and posterior circulation stroke. Knowledge of variations of the great vessels of the neck is important for endovascular interventionists and diagnostic radiologists, more so in the era of new therapeutic op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Blumberg et al reported that an LVA originated from the aortic arch in a patient with an acute intramural hematoma [ 15 ]. In another study conducted by Fridah et al, 84 vertebral arteries were evaluated by CTA in a Zambian population, three of which originated from the aortic arch [ 16 ]. Yamaki et al dissected 515 vertebral arteries in Japanese adult corpses, among which 30 LVAs were noted to originate directly from the aortic arch [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Blumberg et al reported that an LVA originated from the aortic arch in a patient with an acute intramural hematoma [ 15 ]. In another study conducted by Fridah et al, 84 vertebral arteries were evaluated by CTA in a Zambian population, three of which originated from the aortic arch [ 16 ]. Yamaki et al dissected 515 vertebral arteries in Japanese adult corpses, among which 30 LVAs were noted to originate directly from the aortic arch [ 17 ].…”
Section: Discussionmentioning
confidence: 99%